In People Living with HIV (PLWH), Menopause (natural or surgical) Contributes to the Greater Symptom Burden in Women: results from an online US survey - Schnall, Rebecca (Menopause, 2018)
OBJECTIVE: The majority of people living with HIV in the US are now over the age of 50, but symptom burden research has seldom included older women or the potential role of menopause. To examine the influence of menopause as part of sex differences in HIV symptom burden. METHODS: A cross-sectional study was conducted that included both a sex-based analysis of previously reported HIV symptom characteristics of 1342 respondents to an online survey (males, n = 957; female, n = 385) and a follow-up online survey of menstrual bleeding patterns (inferred menopause) in eligible females (n = 242) from the respondent pool. Using linear mixed models, we identified predictors of symptom burden scores in female respondents. RESULTS: For the most troublesome symptoms assessed in the sex-based analysis, depression scores were similar (p>.05), but higher (worse) burden scores for fatigue (p=0.013) and muscle aches/pains (p=.004) were exclusively observed in females after adjusting for covariates. Respondents to the female survey (n=222) were predominantly Black, heterosexual, non-smokers and obese, with an HIV diagnosis of approximately 16 years and at least one co-morbid condition. Burden scores were higher in women reporting amenorrhea due to natural menopause or hysterectomy (n = 104) vs. the menstruating group (n=118) for muscle aches/pains (p=0.05), fatigue (p=0.03), and difficulty falling asleep (p=0.04), independent of age, HIV duration, and # of HIV associated non-AIDS conditions. CONCLUSIONS: Two of the most common symptoms in people living with HIV (PLWH) – fatigue and muscle aches/joint pains - invoke additional burden in women. Independent of aging, symptom burden may be exacerbated after menopause, supporting a shifting paradigm for HIV care management.